Online hemodiafiltration and mortality risk in end-stage renal disease patients: A critical appraisal of current evidence - Helmut Schiffl (The Korean Society of Nephrology, 2019)
The life expectancy of end-stage renal disease patients undergoing regular hemodialysis (HD) remains significantly lower than in the general population. Reducing excess mortality by improving renal replacement options is an unmet medical need. Online post-dilution hemodiafiltration (HDF) has been promoted as the gold standard, offering improved clinical outcomes, based on numerous observational studies that suggest a reduced mortality risk and lower morbidity with HDF compared with standard HD. However, most randomized controlled trials (RCTs) have failed to demonstrate a significant beneficial effect of HDF on all-cause mortality. The effects on secondary outcomes were often negligible or absent. Unfortunately, these RCTs were characterized by a moderate to high risk of bias. In post-hoc analyses of the largest RCTs and meta-analysis of individual participant data from four RCTs, HDF patients receiving the highest convection volume consistently and dose-dependently saw superior outcomes. However, as these studies were not designed a priori to clarify this issue, and there are no indisputable mechanisms underlying reduced mortality risks, we cannot exclude the possibility that the health status of patients (with vascular access as a proxy) may affect outcomes more than the convective technique itself. There is currently insufficient evidence to support the contention that high-volume HDF confers relevant benefits to patients over standard HD. The conflicting data of published RCTs reduce confidence in the superiority of high-volume convective therapy. Hopefully, ongoing large RCTs (for example, CONVINCE) may supply an indisputable answer to the crucial question of high-volume HDF.